ENHANCING EMPATHY THROUGH READ-OUT LOUD ACTIVITY IN SDN SAWOHAN 2 SIDOARJO - Ananda Firda Pratama; Qurrota A'yunin; Tasya Aulia Kuni Masrokhati; Nyoman Sarmi; Kusuma Wijaya; Rindrah Kartiningsih; Rommel Utungga Pasopati (Seminar Nasional Hasil Riset dan Pengabdian, 2026)
This community service program aims to enhance children’s empathy through a read-out-loud activity conducted at SDN Sawohan 2 Sidoarjo. The program was designed to address the need for socio-emotional development alongside literacy skills among children in the community. Read-out-loud sessions were implemented using carefully selected storybooks containing moral values, emotional situations, and social themes relevant to children’s daily lives. The activities involved interactive storytelling, guided discussions, and reflective questions to encourage participants to recognize emotions, understand others’ perspectives, and express their own feelings. Observations and informal feedback indicated increased engagement, improved listening skills, and greater sensitivity toward peers, as reflected in children’s responses and interactions during and after the sessions. The program demonstrates that read-out-loud activities can serve as an effective and accessible method for fostering empathy while simultaneously promoting reading interest. In conclusion, this initiative highlights the important role of community reading spaces in supporting character education and social development in children.